Pengaruh Costumer Experience Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Burger Bangor Tanjung Tabalong - Farhani, Ahmad; Halim, Peter; Febriyanti, Dita (Jurnal PubBis, 2025)
This research is driven by the need to identify factors influencing consumer purchase decisions, particularly within the fast-food business sector. The increasing intensity of competition in this industry necessitates that businesses provide positive customer experiences and maintain product quality to foster loyalty and attract consumer interest. This study aims to analyze the influence of customer experience and product quality on purchase decisions for Burger Bangor Tanjung Tabalong products. Employing a quantitative approach, the research utilizes a survey method involving 96 respondents as the sample. Data were collected through questionnaires comprising three variables: customer experience, product quality, and purchase decisions. Testing was conducted using multiple regression analysis to determine the influence of the two independent variables on purchase decisions, along with validity and reliability tests to ensure the robustness of the research instruments. The findings indicate that both customer experience and product quality significantly influence purchase decisions for Burger Bangor Tanjung Tabalong products. The implications of this study highlight the importance for companies to focus on enhancing customer experience and maintaining product quality to meet consumer expectations. This research offers practical contributions for fast-food outlet managers to formulate marketing strategies that improve both aspects, ultimately increasing customer loyalty and sales.